Mediation Effect of Service Quality on the Relationship of Healthcare Service Innovation and Outpatient Experience - Haeba Ali, Amena; Hasan, Hazmilah; Akmal, Suriati (International Journal of Sustainable Construction Engineering and Technology, 2022)
Healthcare organizations play an important role in people's well-being all over the world; good healthcare facilities are extremely beneficial in combating many diseases worldwide. Innovation is one of the most important factors influencing service quality in healthcare organizations worldwide, particularly in the UAE. The pandemic, changing human needs and globalization have made organizations more aware of the importance of improving patients' experiences through improved service quality and innovative services, which has become a winning strategy and provides organizations with a comparative advantage over others through customer confidence building. This research assessed mediating effect of service quality on health services innovation and outpatient experience. The model was developed with the help of SmartPLS software package and the data was gathered through questionnaire survey. Analysis of 397 questionnaire forms were used to analyze direct relations between service quality and service innovation with out-patient experience as well as indirect effect of service innovation on out-patient experience through service quality. The developed model was confirmed through convergent validity and discirminant validity. The R-square reveals that service innovation accounted for approximately 47% of the variation in service quality. While service innovation and service quality explained approximately 80% of the change in outpatient experience. This means that a unit change in both service innovation and service quality improves the outpatient experience by 80%.